2017
DOI: 10.1292/jvms.17-0083
|View full text |Cite
|
Sign up to set email alerts
|

Combination of vitamin E and vitamin C alleviates renal function in hyperoxaluric rats via antioxidant activity

Abstract: Hyperoxaluria and oxidative stress are risk factors in calcium oxalate (CaOx) stone formation. Supplement with antioxidant could be effective in prevention of recurrent stone formation. The present study aims to evaluate the protective effects of vitamin E and vitamin C in hyperoxaluric rat. The experiment was performed in rats for 21 days. Rats were divided into 5 groups as follows: control (group 1, n=8), hyperoxaluric rats (group 2, n=8), hyperoxaluric rats with vitamin E supplement (group 3, n=7), hyperoxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 28 publications
5
15
0
Order By: Relevance
“…The HLP-induced hyperoxaluria rat model has been used in many previous studies on the pathophysiology of CaOx stone [ 20 , 22 , 23 ]. The BW of rats receiving HLP were not significantly changed, although HLP caused a slightly reduced food intake with a significantly increased water intake, similar to previous studies of hyperoxaluria rats induced by either ethylene glycol [ 48 ] or HLP [ 19 ]. This reflects the deleterious effect of kidney stone on the well-being of rats.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The HLP-induced hyperoxaluria rat model has been used in many previous studies on the pathophysiology of CaOx stone [ 20 , 22 , 23 ]. The BW of rats receiving HLP were not significantly changed, although HLP caused a slightly reduced food intake with a significantly increased water intake, similar to previous studies of hyperoxaluria rats induced by either ethylene glycol [ 48 ] or HLP [ 19 ]. This reflects the deleterious effect of kidney stone on the well-being of rats.…”
Section: Discussionsupporting
confidence: 86%
“…Accordingly, Klotho gene transcription/translation could be regulated by oxidative stress. An enhanced oxidative stress level was indicated by the increased PMDA level, which has been reported previously in the hyperoxaluric rat model [ 19 , 44 ] and in vitro studies [ 41 , 42 ] as well as in CaOx stone patients [ 18 ]. In addition, in this present study, kidney oxidative stress was likely to have been increased since an elevated level of kidney MDA and SOD activity levels, and a diminished level of GSH was found.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Accumulated crystals in the tubular basement membrane further induce reactive species generation. Several studies have shown that the supplement of antioxidants, including vitamin, flavonoids, polyphenol and other phytonutrients ameliorated renal injury and stone formation in urolithiasis patients . In the present study, we demonstrated that LPR reduces plasma protein carbonyl, and increases U‐TAS.…”
Section: Discussionsupporting
confidence: 67%